21st Century Competition: State & Conglomeration-Driven Capitalism - Widjanarko, Yeremia (Economics Departement, Faculty of Business and Economics, Universitas Surabaya, 2025)
Indonesia needs to choose an economic model in order to realise its target of 8% GDP growth under Prabowo Subianto’s incoming administration. This paper compares both China’s state capitalism and South Korea’s conglomerate-driven capitalism for their relevance to Indonesia. China’s model, with a significant state intervention and SOEs prominent role, greatly driven industrialisation and average of 9% GDP growth over 30 years. Whilst South Korea’s model, dominated by conglomeration, focuses more on innovation in tech and exports, thus achieving a stable 4% average GDP growth. Employing data from the World Bank on FDI, exports, and GDP in constant 2015 USD, this paper examines both of these models using the Comparative Political-Economy framework. The findings showed that the China’s state capitalism to be more suitable for Indonesia due to capability of managing a large scale economy and the need of centralisation of resource control, infrastructure development and economic transitions. The blending of state control and market dynamics offers flexibility to tackle challenges in the economy. Nevertheless, the issues of inefficiencies must be in concern.